Realizing human rights in rural Punjab of India: a study of enforcement of selected human rights - Pathak, Puneet; Nandini, Vagisha; Yadav, Deepesh; Kaur, Sukhwinder; Sen, Rajinder Kumar; Riang, Shanti (Frontiers in Sociology, 2025)
The realization of human rights assumes great significance in the context of India, the largest democracy in the world. Being a state party to binding international human rights covenants, India is obligated to take measures to ensure the realization of human rights by its citizens. With over 64% of its population residing in the villages, the panchayati raj institutions assume a crucial role in the realizing of human rights, considering their proximity to the rural population. The study's objective is to analyze the status of realization of selected human rights in terms of the ‘respect, protect, fulfill and promote' framework, i.e., health, education and political participation in the selected Gram panchayats of Indian Punjab. The study adopted a quantitative approach, and primary data were collected through survey questionnaires from members of selected Gram Panchayats and beneficiaries availing the benefits of related governmental schemes. The study offers insights into the degree to which the state obligations regarding the selected human rights are being upheld and how the variation can be explained. The result revealed inconsistencies between the claims of panchayat members and the beneficiaries' experiences. The study exposed deficiencies in infrastructure and service delivery across the rights. The study recommends improving awareness and satisfaction regarding the National Rural Health Mission (NRHM) and the Samagra Shiksha Abhiyan schemes for fulfilling the rights to health and education. Enhanced efforts are needed to promote these rights through regular awareness campaigns and discussions at Gram Sabha meetings. Furthermore, there is a need to strengthen campaigns for electoral participation, ensuring consistent and well-communicated Gram Sabha meetings, and active facilitation of the political involvement of marginalized groups for the effective realization of the right to political participation.